A new species of the genus Cenocorixa (Hemiptera, Heteroptera, Corixidae) from China - Tong-Yin Xie; Guo-Qing Liu (ZooKeys, 2021)
A new species of the genus Cenocorixa Hungerford (Hemiptera, Heteroptera, Corixidae) is described from China. Cenocorixa yuanjiangensis sp. nov. is reported from Yunnan Province. An updated key to the Chinese species of Cenocorixa is presented.